INTRODUCTION OF WILD SPECIES AND VARIETIES OF TULIPA L. IN THE CONDITIONS OF THE SOUTH-EAST OF KAZAKHSTAN (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
The most promising 3 wild-growing species Tulipa Ostrowskiana Regel, Tulipa Kolpakowskiana and Tulipa tarda Stapf and 7 varieties of tulips Jumbo Pink, Sinaeda King, Shirley Double, Wild Tulipen Saxatilis, Monsella, Salmon Prince introduced in the Main Botanical Gardenare promising for landscaping in the South-East of Kazakhstan. Currently, the problem of landscaping is one of the urgent problems. In this regard, tulips arepromising for creating spring-flowering flower beds in the cities of Kazakhstan. Their diversity incolor of the flower and the height of the peduncles allows you to create bright, spectacular groupson the streets of the city.
Keywords: introduction, varieties of tulips, wild species.